The Use of Substances Other Than Nicotine in Electronic Cigarettes Among College Students - Deric R Kenne; Rebecca L Fischbein; Andy SL Tan; Mark Banks (SAGE Publishing, 2017)
Introduction: Electronic cigarettes (e-cigarettes) have grown in popularity, especially among youth and young adults. Although e-cigarettes were originally intended to vaporize a liquid mixture containing nicotine, there appears to be an increasing trend in other substance use in e-cigarettes (OSUE). Materials and methods: Cross-sectional data from 1542 undergraduate college student e-cigarette users from a large Midwestern university were collected via online survey to assess prevalence of e-cigarette use, reasons for use, perceived harm, and prevalence and predictors of OSUE. Results: Nearly 7% (6.94%) reported using an e-cigarette to vaporize and inhale a substance other than nicotine. Current tobacco cigarette smokers were significantly more likely to report OSUE (51.0%) as compared with never (33.7%) and former (15.4%) smokers. Among respondents reporting OSUE, the primary reason for e-cigarette use was "safer than cigarettes" (21.7%), followed by "experimentation" (18.9%) and "friends use" (17.0%). Most (77.9%) reported using cannabis or some derivative of cannabis in an e-cigarette. Binomial logistic regression found that women were less likely to report OSUE by a factor of 0.60, former tobacco cigarette smokers as compared with never smokers were more likely to report OSUE by a factor of 1.87, and e-cigarette users who reported using e-cigarettes for "cool or trendy" reasons were more likely to report OSUE by a factor of 2.89. Discussion: Little is known regarding the health effects of cannabis and cannabis derivatives delivered through e-cigarettes. Concern may also be warranted regarding the potential dangers of this young population using substances more dangerous than cannabis in e-cigarettes. Knowledge is limited regarding the public health impact of vaping cannabis or other illicit substances among college student populations. This study stresses the need for continued research regarding the vaping of cannabis and other illicit substances among college students.